TI_GERICHTE 12.2023.147 vom 10. Januar 2024 , Esecuzione di una transazione conciliativa, reclamo privo d'oggetto - TI Tribunale d'appello (2024)
Esecuzione di una transazione conciliativa, reclamo privo d'oggetto